Kandidat Ideal atau Populis?: Strategi Framing Visual Ganjar Pranowo dan Puan Maharani Melalui Instagram - Febryanti, Dian Rousta; Ahmad, Nyarwi (Jurnal Komunikasi, 2023)
Self-presentation and visual branding strategy through social media, particularly Instagram, have been increasingly developed by Indonesia’s public figures, including Ganjar Pranowo and Puan Maharani. This article examines what types of personal brand visualized by these public figures through their Instagram accounts in between 1 August and 25 October 2022. Having adopted political marketing perspective, we adopt Munoz and Towner’s (2017) two concepts of framing personal brand visualisation, which are framing visualisations as an ideal candidate and as a populist candidate. Extraction of material posted in their Instagram accounts using Grabe and Bucy’s (2009) visual framing analysis reveal the following findings. Ganjar Pranowo favoured visualing his personal brand not merely as an ideal candidate, but also as a populist candidate. Puan Mahanari instead, preferred visualising her personal brand as an ideal candidate. In contrast to Ganjar, Puan seems being less capable of developing her personal brand using a visual frame as a populis candidate. These evidence that self presentation and branding performed by public figures using visual elements through social media platforms indicate the degree to which did these public figires have capability in visualising their personal brand as an ideal and/or a populist candidate when they address the electoral markets.